FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN RAWAT INAP ULANG DIRUMAH SAKIT PADA PASIEN CHF - Fatoni ' Widagdo; Darwin ' Karim; Riri ' Novayellinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this study was to determine the factors associated with the incidence of re-hospitalization in the hospital for client with CHF. This study is a correlative study with cross-sectional design.This research was conducted at Flamboyan room (cardiology ward) General Hospital Arifin Achmad Pekanbaru involving 30 respondents. The sampling method is purposive sampling. Measuring instrument used was a questionnaire that has been tested for validity and reliability. This study used univariate and bivariate analysis. The results showed that are the relationship between (p value =0.000), history of hypertension (p value =0.009), medication therapy adherence(p value =0.014), dietary adherence(p value =0.537) and the adequacy of activity and rest(p value =0.030) with  hospitalization incidence on CHF patients. The results of this study recommends hospital to provide health education  involving factors associated with the incidence of re-hospitalization client CHF.   Keywords: Client  , CHF, re-hospitalization